2018
DOI: 10.1039/c8nr02198h
|View full text |Cite
|
Sign up to set email alerts
|

Bi-metallic boride electrocatalysts with enhanced activity for the oxygen evolution reaction

Abstract: Rational design and understanding of the intrinsic mechanism are critical to develop highly active and durable electrocatalysts. In this study, a series of bi-metallic boride catalysts based on Ni and Co were prepared, and their activities were evaluated. The synthesised Co-10Ni-B catalyst exhibited excellent activity for water splitting in a 1 M KOH electrolyte. The overpotential was 330 mV at a current density of 10 mA cm-2, better than previously reported mono-metallic borides and even IrO2. The synergistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 39 publications
4
53
0
Order By: Relevance
“…The interaction between Co and H is too strong in Co–P, but in Co–P–B, the bonding is optimized owing to the transfer of electrons from B to Co, thereby increasing HER activity. Apart from these elements, HER activity of many other ternary catalysts has been reported, but no efforts were taken to understand the role of incorporated metals.…”
Section: Origin Of Electrochemical Activity In Metal Boridesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between Co and H is too strong in Co–P, but in Co–P–B, the bonding is optimized owing to the transfer of electrons from B to Co, thereby increasing HER activity. Apart from these elements, HER activity of many other ternary catalysts has been reported, but no efforts were taken to understand the role of incorporated metals.…”
Section: Origin Of Electrochemical Activity In Metal Boridesmentioning
confidence: 99%
“…This manifested the suitability of Co–Ni–B in particular, and Co‐based borides in general, for alkaline water electrolysis. The group of Zhang et al also synthesized Co–Ni–B and found that the molar ratio of Ni/(Ni + Co) = 10% yields the best performance for OER in 1 m KOH. Co–Ni–B supported on Ni foam, carbon cloth and rGO were reported by different groups in a bid to lower down the overpotential.…”
Section: Strategies Adopted To Enhance the Performance Of Metal Boridesmentioning
confidence: 99%
“…At present, noble metal–based materials for OER, such as ruthenium oxides, are still ranking the highest level. [ 16,17 ] Meanwhile, nonnoble metal compounds, for instance, transition metal oxides, [ 18–21 ] perovskite, [ 22,23 ] hydroxide, [ 24,25 ] nitrides, [ 26,27 ] borates, [ 28,29 ] and so on, have also captured extensive interests for preparing high‐efficient OER catalysts. Among them, the metal fluoride, mostly literature reported for supercapacitor, lithium ion battery, etc., [ 30–33 ] is rarely wielded in the field of water electrolysis, possibly due to the chemical/electrochemical instability of fluoride ions and the weak bond between the metal ions and fluoride ions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2c shows the HRXPS spectrum of B 1s, which can be deconvoluted into two sub-peaks located at 187.9 and 191.9 eV BE, ascribed to the BM and BO bond mainly due to B 2 O 3 and other boron-oxo species, respectively. [14] The presence of B interacting with metals which are catalytic active sites implies electron transfer to the d bands of the transition metal from B as revealed by a positive shift in BE compared to elemental B (187.2 eV), [10a] and as consequence, metal atoms are electron-rich which makes them highly active for catalytic reactions. [14] The presence of B interacting with metals which are catalytic active sites implies electron transfer to the d bands of the transition metal from B as revealed by a positive shift in BE compared to elemental B (187.2 eV), [10a] and as consequence, metal atoms are electron-rich which makes them highly active for catalytic reactions.…”
mentioning
confidence: 99%